Experience in using «anchor marks» for preoperative marking of small-diameter intra-pulmonary peripheral neoplasms - I. V. Dmitrochenko; E. E. Fufaev; I. I. Dzidzava; D. A. Yasyuchenya; O. V. Barinov; V. A. Popov; B. A. Kotiv; A. A. Safronova (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to evaluate the effectiveness of the use of preoperative transthoracic insertion of an «anchor mark» as a marker of a small intra-pulmonary pathological site for performing atypical videothoracoscopic resection (biopsy).MATERIALS AND METHODS. The study included 15 patients with solitary peripheral lung neoplasms of small diameter (8 [6; 10] mm). All neoplasms were located in the intermediate zone of the pulmonary parenchyma.RESULTS. In 9 (60 %) patients, according to cito-biopsy data, tumor cells were detected in the studied preparation, which served as a reason for performing endovideosurgical anatomical lung resection – lobectomy, in 2 (13.3 %) patients, hamartoma was detected and, thus, atypical lung resection proved to be a sufficient volume of surgical intervention, in 4 (26.7 %) patients, areas of local pneumofibrosis were verified, which made it possible to complete surgery at the diagnostic stage. The average duration of marking of the pathological focus was 25 minutes, atypical videothoracoscopic lung resection was 30 minutes. There were no access conversions.CONCLUSION. Preoperative transthoracic marking by means of the «anchor marks» system is a safe and highly effective navigation method for atypical resection (videothoracoscopic biopsy) of small-diameter lung neoplasms.